Impact evaluation of educational cash transfer programs on college students’ academic performance in the Philippines - Bradecina, Jan Blademir D.; Campo, John Marc; Leonardo, Kent Wisson S.; Onsay, Emmanuel A. (Dynamics of Rural Society Journal, 2025)
Despite facing severe poverty, many college students continue to pursue higher education, viewing a bachelor’s degree as essential to achieving success and lifting their families out of poverty. However, the extent to which the Educational Cash Transfer (ECT) Program supports their academic performance remains unclear. This study aims to evaluate the effectiveness of the ECT Program, particularly among beneficiaries of the Pantawid Pamilyang Pilipino Program (4Ps), compared to non-4Ps students, using Randomized Controlled Trials (RCT). Data were gathered through questionnaires and secondary sources and analyzed using frequency counts, percentage analysis, Likert scale analysis, t-tests, and regression discontinuity design (RDD). The findings suggest that the Assistance to Individuals and Families in Crisis Situations (AICS) program plays a significant role in addressing students' financial needs. However, challenges such as delays in ECT distribution, stringent qualification requirements, cumbersome release procedures, and issues with document submission hinder effective access. Most respondents expressed satisfaction with the ECT Program, citing improvements in academic performance and timely submission of schoolwork. Notably, 4Ps membership significantly influenced student attendance, especially among first-year students who showed the highest punctuality. Although eligibility for ECT positively affects academic outcomes, the lack of statistical significance highlights limitations in its measurable impact. Based on the findings, the study recommends continuing and expanding the ECT Program with increased funding to support college, high school, and elementary students. It also urges improvements in fund disbursement processes by streamlining procedures, enhancing inter-agency coordination, and setting clear timelines to ensure timely delivery of aid. These insights provide valuable guidance for local government units and stakeholders seeking to enhance access to educational financial assistance.